Pre transplant workshop of donor and recepient in the first kidney transplant in Sri Lanka - De Mel, W.C.P.; Sheriff, M.H.R. (My University, 1996)
Mr. Lituss Thirimanne a 38 year old hospital attendent was seen in the University Medical Unit in April 1985, In advanced chronic renal failure due to chronic glomerulo-nephritis his blood urea at this time was 176mg% and the creatinine was 5.1 mg and had a supine blood pressure of 180/ I00-110. He was conservatively on, diet and supplementation, antihypertensives - methyldopa, hydralazine, cimetidine . He continued to deteriorate in spite of conservative treatment. He had an arteriovenous fistule created in his (L) wrist and referred to the Private Renal Unit at Lanka Medicare Co. for chronic haemodialysis as no chronic haemodialysis is possible at G. H. Colombo. He was started on regular dialysis therapy on 27.8.85, and had 13 regular haemodialysis treatments over a 6 week period.Informed written consent was obtained from both the recepient and the donor following family counseling. Mr. Charles Thirimanne his 66 year old father was then admitted to the University Medical Unit and a thorough physical examination done. Screening haematologlcal and cardiovascular investigations and a liver profile were carried out. More extensive renal function tests including microbiological, biochemical and radiological (tests,Including) IVU. Renal arteriography was performed. He was found to be Australia Antigen negative. The tissue typing was done with the Royal Free Hospital laboratory collaboration. The medical, surgical, dialysis and nursing and the ancillary services teams met and the final preparations made for the transplant. The recipient was then specially prepared Pre-transplant by Increasing the dialysis frequency giving blood transfusions and biochemically assessed and found to be satisfactory. Both donor and recipient were admitted to the Ratnams Private Hospital on the evening of 4.10.1985 and the preopanaesthetic assessment was carried out and surgery fixed up for 5.10.85. The recipient had preoperative immunosuppression commenced few hours before operation